Learning Scorecard dashboards: visualizing student learning experience - Cardoso, E. (2019)
This paper presents the design of dashboards for the Learning Scorecard, a platform designed for improving the student experience in a Higher Education course using gamification and Business Intelligence (BI) techniques. LS is a Learning Analytics application, that has been used in Data Warehouse and BI courses in a University setting since 2016. The LS platform has two independent views: student view and faculty (or course coordinator) view. In the LS faculty view, dashboards were designed according to the best practices of information visualization for decision support, whereas in the student view the visualization of the learning experience is immersed in gamification elements. This paper focuses only on student dashboards, which are driven by engagement and motivation of students to improve their collaboration and learning experience. A central design decision for the LS implementation, was the recognition that the way students want to track their progress and their learning experience in a course is fundamentally different that the way teachers need to monitor student progress. The presented learning dashboards use gamification mechanisms to enable the visualization of self-assessment results giving a clear indication of the learning progress of students in a course.